2018
DOI: 10.1101/508192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic suppression of proteolipid protein rescues Pelizaeus-Merzbacher Disease in mice

Abstract: 14 15 Mutations in proteolipid protein 1 (PLP1) result in failure of myelination and severe 16 neurological dysfunction in the X-linked pediatric leukodystrophy Pelizaeus-Merzbacher 17 disease (PMD). The majority of PLP1 variants, including supernumerary copies and various 18 point mutations, lead to early mortality. However, PLP1-null patients and mice display 19 comparatively mild phenotypes, suggesting that reduction of aberrant PLP1 expression 20 might provide a therapeutic strategy across PMD genotypes. H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In vitro and in vivo studies have also been completed using CRISPR-Cas9 to correct mutations associated with Huntington's disease, with promising results demonstrating that suppression of mutant alleles can alleviate motor phenotypes in mice (Shin et al, 2016;Kolli et al, 2017;Monteys et al, 2017;Yang et al, 2017). In the field of HLDs, a recent study has demonstrated that CRISPR-Cas9 mediated germline suppression of Plp1 in the severe jimpy mouse model of Pelizaeus-Merzbacher disease leads to increased myelination and restored lifespan (Elitt et al, 2020). Most recently, the first clinical trials of CRISPR-Cas9 therapies have launched, with ex vivo approaches centering around cancer immunotherapy, as well as gene disruption of hematological disorders including sickle-cell anemia and β-thalassemia (Li et al, 2020;Rosenblum et al, 2020;Uddin et al, 2020).…”
Section: Crispr-cas9 Editing Systemmentioning
confidence: 99%
“…In vitro and in vivo studies have also been completed using CRISPR-Cas9 to correct mutations associated with Huntington's disease, with promising results demonstrating that suppression of mutant alleles can alleviate motor phenotypes in mice (Shin et al, 2016;Kolli et al, 2017;Monteys et al, 2017;Yang et al, 2017). In the field of HLDs, a recent study has demonstrated that CRISPR-Cas9 mediated germline suppression of Plp1 in the severe jimpy mouse model of Pelizaeus-Merzbacher disease leads to increased myelination and restored lifespan (Elitt et al, 2020). Most recently, the first clinical trials of CRISPR-Cas9 therapies have launched, with ex vivo approaches centering around cancer immunotherapy, as well as gene disruption of hematological disorders including sickle-cell anemia and β-thalassemia (Li et al, 2020;Rosenblum et al, 2020;Uddin et al, 2020).…”
Section: Crispr-cas9 Editing Systemmentioning
confidence: 99%